2011
DOI: 10.1111/j.1460-9568.2011.07909.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue‐induced increase in intracortical communication between mid/anterior insular and motor cortex during cycling exercise

Abstract: In the present study, intracortical communication between mid/anterior insular and motor cortex was investigated during a fatiguing cycling exercise. From 16 healthy male subjects performing a constant-load test at 60% peak oxygen consumption (VO(2peak)) until volitional exhaustion, electroencephalography data were analysed during repetitive, artefact-free periods of 1-min duration. To quantify fatigue-induced intracortical communication, mean intra-hemispheric lagged phase synchronization between mid/anterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 62 publications
4
45
0
Order By: Relevance
“…It has been suggested that lactate may act as a signal to the CNS and influence the RPE response to exercise (Hampson et al, 2001). In this model, lactate and other peripheral signals would be perceived by group III and IV muscle afferents, stimulating sensorial areas in the brain (e.g., mid/anterior insular), which in turn could increase RPE and influence the motor cortex (Hilty et al, 2011). However, fatigue does not appear to be associated with lactate accumulation, but rather with changes in pH (Gladden, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that lactate may act as a signal to the CNS and influence the RPE response to exercise (Hampson et al, 2001). In this model, lactate and other peripheral signals would be perceived by group III and IV muscle afferents, stimulating sensorial areas in the brain (e.g., mid/anterior insular), which in turn could increase RPE and influence the motor cortex (Hilty et al, 2011). However, fatigue does not appear to be associated with lactate accumulation, but rather with changes in pH (Gladden, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Quantifying these cortical activity changes during hypoxic exercise would help us identify the specific regions of interest, perhaps even help locate an ''origin'' of central fatigue in the brain. Some early promising work by Hilty et al (2011aHilty et al ( , 2011bHilty et al ( , 2011c indicates that muscle fatigue leads to changes in interaction between mid/ anterior insular, thalamus, and the motor cortex.…”
Section: Future Perspectivesmentioning
confidence: 98%
“…Thus, it removes the instantaneous component, which is driven by non-physiological effects and intrinsic physical artifacts that occur due to volume conduction and low spatial resolution (Nolte et al 2004;Stam et al 2007;Schoffelen and Gross 2009;Pascual-Marqui et al 2011). Accordingly, lagged phase synchronization has been increasingly used in recent studies (Canuet et al 2011;Hilty et al 2011;Canuet et al 2012;Guggisberg et al 2014;Kühnis et al 2014;Olbrich et al 2014;Ramyead et al 2014;Steinmann et al 2014;Elmer et al 2015;Vecchio et al, 2015) and has received cross-modal validation by studies combining EEG-based lagged phase synchronization measurements with MRI-based diffusion tensor imaging (Vecchio et al 2015).…”
Section: Lagged Phase Synchronization Of Neuronal Oscillationsmentioning
confidence: 98%